TEMPORARY ECONOMIC CRISES - Karimzadi, Shahzavar ([S.l.] : ROUTLEDGE, 2022)
In traditional theory of economic crisis, and in all its manifestations, there is no fundamental difference between economic disorder and economic crisis: the two types of economic turmoil are both considered temporary states. This book is a methodical study of deep-seated causes of economic crises. The aim of the book is to explain the key difference between economic disorder and economic crisis. Its key argument is that economic disorder is a permanent condition, whereas economic crises are a series of transitory periods. Economic crises, unlike economic disorders, are acute and frenzied volatilities that are unpredictable and short-lived. Humans cannot survive in a condition of perpetual economic crises but can only accommodate life under unremitting economic disorders. The book also explores the root cause of economic crisis. Unlike the received wisdom in economics, this book looks at the root cause of such hysterical economic turbulences as a result of an innate propensity of human fallibility. The final section of this book looks at the ramifications of this alternative perspective on macroeconomic policy formation and implementation. This book is a major contribution to the literature on economic disorder and crises and will be of great interest to readers of economic theory, philosophy of economics, and the history of economic thought.
Keywords: Economics; Financial crises; Economic history; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General